Two-Stage Integrated Ceramic Membrane Reactor System For The Continuous Enzymatic Synthesis Of Oligosaccharides - Ebrahimi, Mehrdad; Placido, Laura; Engel, Larisa; Shams-Ashaghi, Kikavous; Czermak, Peter (Filtech Exhibitions Germany, 2010)
A new type of ceramic membrane reactor is proposed for the continuous enzymatic synthesis of oligosaccharides using native enzyme. Beta-Galactosidase (EC 3.2.1.23) catalyses the hydrolysis of lactose to the monosaccharides glucose and galactose and also the transgalactosylation reaction to produce galactosyloligosaccharides (GOS). GOS are non-digestible oligosaccharides which are recognized as prebiotics. GOS consist of a number of oligosaccharides with varying ß-glycosidic linkages depending on the enzyme source. In this work, the results for the continuous production of GOS from lactose by means of physically-confined ß- Galactosidase in a novel ceramic membrane reactor system are presented.
Keywords: Ceramic membrane; Membrane reactor; Ultrafiltration; Cross-fFlow filtration; Lactose